Applications and Major Achievements of Genome Editing in Vegetable Crops: A Review - Kim, Young-Cheon; Kang, Yeeun; Yang, Eun-Young; Cho, Myeong-Cheoul; Schafleitner, Roland; Lee, Jeong Hwan; Jang, Seonghoe (Frontiers in Plant Science, 2021)
The emergence of genome editing technology has allowed manipulation of DNA sequences in genomes to precisely remove or replace specific sequences in organisms resulting in targeted mutations. In plants, genome editing is an attractive method to alter gene functions to generate improved crop varieties. Genome editing is thought to be simple to use and has a lower risk of off-target effects compared to classical mutation breeding. Furthermore, genome editing technology tools can also be applied directly to crops that contain complex genomes and/or are not easily bred using traditional methods. Currently, highly versatile genome editing tools for precise and predictable editing of almost any locus in the plant genome make it possible to extend the range of application including functional genomics research and molecular crop breeding. Vegetables are essential nutrient sources for humans and provide vitamins, minerals and fiber to diets, thereby contributing to human health. In this review, we provide an overview of the brief history of genome editing technologies and the components of genome editing tool boxes, and illustrate basic modes of operation in representative systems. We describe the current and potential practical application of genome editing for the development of improved nutritious vegetables and present several case studies demonstrating the potential of the technology. Finally, we highlight future directions and challenges in applying genome editing systems to vegetable crops for research and product development.